Spatial and temporal frequency band changes during infarct induction, infarct progression, and spreading depolarizations in the gyrencephalic brain - Kentar, Modar; Díaz-Peregrino, Roberto; Trenado Colin, Carlos Alberto; Sánchez-Porras, Renán; San Juan Orta, Daniel; Ramírez-Cuapio, Francisco L.; Holzwarth, Niklas; Maier-Hein, Lena; Woitzik, Johannes; Santos, Edgar (Frontiers in neuroscience, 2022)
To describe the spatial and temporal electrocorticographic (ECoG) changes after middle cerebral artery occlusion (MCAo), including those caused by spreading depolarization (SD) in the pig brain.